Liminal femininity - Mrak, Anja (ELOPE (Ljubljana), 2022)
The article examines the liminal nature of the two central female characters in Louise Erdrich’s novel Tracks. Despite appearing as opposites, Fleur and Pauline, members of the Chippewa tribe, are both portrayed as socially abject and victims of the inexorable social transformation brought about by American imperialism to establish patriarchy and capitalism. Enhanced through magical realism, their animality and monstrosity call attention to a liminal femininity trapped in a social order that seeks to subjugate it. The novel also considers female sexual agency and different modes of exerting and losing control in encounters defined by sexual objectification and the male gaze. Fleur’s and Pauline’s stories demonstrate how the female body becomes a site of colonial enterprise, which devalues, exploits, and nearly eradicates the Native American community, their culture, and philosophies.
Keywords: animaličnost; animality; Erdrich, Louise; feminism; feminizem; magical realism; magični realizem